Effects of various poisoning compounds on the activity and stereospecificity of heterogeneous Ziegler–Natta catalyst - Kitti Tangjituabun et al (Science and Technology of Advanced Materials, 2008)
A TiCl4/ethylbenzoate/MgCl2 Ziegler–Natta catalyst was pretreated with chemically different poisoning compounds to investigate their effects on the catalyst activity and stereospecificity for propylene polymerization. The poisoning power on the activity was in the order of methanol > acetone > ethyl acetate. A kinetic analysis using the stopped-flow method revealed that addition of the poisoning materials decreased the activity through the reduction of the number of active sites, whereas the catalyst isospecificity was hardly affected by these materials.